The efficiency of credit operations of Department of Engineering and Public Works Savings and Loan Association Inc., as perceived by its members for the year 2002 - Baler, Maureen S. et. al. 4 0 16; 5 (2002)
u
Research Paper: (BSBA major in Banking and Finance) - Pamantasan ng Lungsod ng Maynila, 2002.
Keywords: 2 -- 0; 6; 20; 20; 2